2006
DOI: 10.4028/www.scientific.net/amr.15-17.525
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Sensitivity Study of the Induction Hardening Process

Abstract: Induction heating is a case hardening process used to improve performance of machine components by producing a hard martensitic microstructure and high compressive residual stresses at the surface layer. A reliable numerical model able to predict the hardness profile would shorten process development. However, the accuracy and the efficiency of the model are restricted by the coupling complexity between the electromagnetic and thermal fields, and the nonlinear behaviour of the material properties. The paper an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…This mesh contains 335,024 elements and 838,747 degrees of freedom. A parallel study showed that it is necessary to keep the actual geometry of the coil instead of a simplified rectangular section [7][8].Fig. 1 shows the distributions of the induced current density and temperature after 0.5 s in the MF case(10 kHz).…”
Section: Table 1 Electromagnetic and Thermal Properties Electromagnet...mentioning
confidence: 99%
“…This mesh contains 335,024 elements and 838,747 degrees of freedom. A parallel study showed that it is necessary to keep the actual geometry of the coil instead of a simplified rectangular section [7][8].Fig. 1 shows the distributions of the induced current density and temperature after 0.5 s in the MF case(10 kHz).…”
Section: Table 1 Electromagnetic and Thermal Properties Electromagnet...mentioning
confidence: 99%
“…Friesenbichler et al (2006) pointed out the sensitivity of material data on phase transformation and residual stresses during hardening. Recently, Mirzaee-Sisan et al (2007), Barka et al (2007), Li et al (2007), and attempted the sensitivity studies for fitting the experimental results. This work introduces a simple sensitivity analysis which reveals the impact of important material properties on the distortion and residual stresses.…”
Section: Introductionmentioning
confidence: 96%
“…the frequency of the current applied 5 or parameters of the materials used as susceptors. 6,7 Regarding the cure kinetics of paste adhesives, there are different models defining the relation between temperature, time and the degree of cure; mainly based on combinations of autocatalytic and n-th order reactions that are selected depending on the type of resin or adhesive under study. 8 The characterization of the cure kinetics is typically carried out by fitting DSC measurements of the adhesive or resin to the theoretical model, obtaining specific parameters for each material.…”
Section: Introductionmentioning
confidence: 99%